Inventory of introduced fish species traded in Medan Regency, North Sumatra, Indonesia - Batubara Agung Setia; Panggabean Anastasya Sorta; Rahmatsyah Rahmatsyah; Juliani Rita; Syarifuddin Syarifuddin; Muliari Muliari; Akmal Yusrizal; Irfannur Irfannur (BIO Web of Conferences)
Reports regarding introduced fish species traded in Medan have never been reported, even though the invasive impact of several species has occurred, especially in Lake Toba, North Sumatra. This research aims to collect data on the introduced fish species traded in Medan, North Sumatra, Indonesia. This research used a survey method by collecting data on introduced fish in 30 aquarium shops. The research was conducted from March to May 2024. The identified fish were then assessed for their frequency to determine their distribution percentage in aquarium shops in Medan. The results of the analysis showed that there were 55 species of introduced fish traded in Medan City which were classified into 46 genera, 29 families, 14 orders. The order Cichliformes dominates the number of species reaching 20%, followed by Cypriniformes 18%, Characiformes 13%, Siluriformes 13%, Osteoglossiformes 9%, Anabantiformes 6%, Cyprinodontiformes 5% and others 16% (species < 3%).